The Role of Islamic Boarding School (Pesantren) Education in Enhancing University Students’ Intellectual Development - Taufikin, Taufikin; Rofi’ah, Khafidzotur; Rahmadani, Amelya; Sa’diyah, Nabila Farihatus; Maharani, Latifah Dwi (ISTIFHAM, 2025)
The changing paradigm of higher education in the modern era demands the integration of intellectual and spiritual development among university students. However, many educational institutions still separate these two dimensions, resulting in a gap between academic knowledge and moral character formation. This study aims to analyze the role of Islamic boarding school (pesantren) education in enhancing students’ intellectual capacity through an integrative approach grounded in Islamic values. Employing a descriptive qualitative design, the research utilized in-depth interviews, participatory observations, and documentation involving one pesantren head, four teachers, and twelve university students at the An-Nasuchiyah Student Islamic Boarding School in Kudus, Central Java. The findings reveal that pesantren education plays a strategic role in fostering critical thinking, self-regulated learning, and autonomy through the integration of religious and academic activities. Intellectual traditions such as classical text studies (kajian kitab), bahtsul masā’il (collaborative scholarly deliberation), and muhadharah (public speaking practice) not only strengthen religious literacy but also cultivate analytical and argumentative reasoning skills. The pesantren’s disciplined routines and communal life effectively nurture resilience, social awareness, and ethical consciousness among students. This study underscores pesantren as a holistic educational model that harmonizes spirituality, intellectuality, and morality as the foundation for developing ethically grounded academic individuals. The study concludes that pesantren must continue adapting to technological innovation and research-based curricula to remain relevant in the digital era